Antimicrobial evaluation of modified herbal and allopathic dental rinse solution against virulent strains. - Yacoob Bawa, Mariyah; Aqeel, Afsheen; Asif, Saima; Bano, Saeeda; Abbas, Tanveer (International Journal of Endorsing Health Science Research, 2021)
Background: Mouthwashes are antiseptic solutions and produce anti-inflammatory properties against periodontal infections in humans. Several in-vitro studies have been performed against virulent strains, as evidenced by an appropriate knowledge about their quality, effectiveness and safety in this research. This study is designed to test the antimicrobial effects and evaluation of mouthwashes against pathogens involved in dental caries and oral infections. Methodology: Rinse solution (Mouthwash) has been developed by three different formulations. Anti-caries solutions were applied and checked against virulent bacterial and fungal pathogens. The antimicrobial effectiveness was identified using the agar well diffusion method and minimum inhibitory concentration (MIC). Results: Chemisol showed potential killing activity and a zone of inhibition against pathogens ranging in 21-30 mm, which comparatively have higher zones than biosol and herbisol. Biosol also indicated efficacy within 11-13 mm zone of inhibition against Salmonella typhi ATCC-14028, Salmonella enterica ATCC-6017 resistant to herbisol and chemisol. Moreover, biosol exhibited greater MIC against most microorganisms at direct concentration and 1:10 dilution compared to herbisol and chemisol. Conclusion: The significant difference observed in the antimicrobial activities of herbal, herbal & allopathic combination and allopathic dental washes against pathogenic strains. This study concluded that proper gargling with mouth wash solutions reduces the risk of life-threatening strains from fecal water & food.